Comparing Student Creativity Skills in Experiment-Based and Project-Based Science Learning - Dewanti, Binar Ayu (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
This study aims to determine the comparison of students' creativity skills in experiment-based science learning and project-based science learning. This research is an experimental study with a posttest only control group design. The population of this study was class VII SMPN 2 Sugio, totaling 157 people (from class VII-A to VII-F). The method of obtaining data in this study is the method of observation and documentation. Methods of data analysis were carried out by testing for normality and homogeneity, as well as testing hypotheses by using independent sample t-test with the help of SPSS 18 for Windows. From this research it can be concluded that there are differences in the creativity skills of students in project-based learning and experiment-based learning, where the average value of creativity skills in project-based learning is greater than the average creativity skills in experiment-based learning.